Quality of service in real estate projects and the profitability of construction companies in the district of El Tambo Huancayo-2018 - Espinoza Landa, Rosario Pilar (2020)
Currently there is consensus regarding the quality of service and profitability in real estate projects in Peru, these two concepts combine as fundamental variables within an organizational management, however, it is not clear the knowledge of what are the specific effects that these have variables in achieving a better valuation of construction companies in general. That is why the researcher posed the question How does the quality of service in real estate projects influence the economic profitability of Construction Companies in the District of El Tambo 2018 ?, which at the same time gave rise to the hypothesis: The quality of service would significantly influence the profitability of the real estate projects of the Construction Companies in the District of El Tambo 2018., to demonstrate this hypothesis, information was collected through the application of a questionnaire of 15 questions to 12 employees of the Construction Company Consortium Architects & Engineers located in the district of El Tambo, this survey was answered individually under strict confidentiality, as well as an analysis sheet of the two-year financial statements of the same unit of analysis Consorcio Arquitectos & Ingenieros SAC, the analysis was prepared of these documents allowed to observe the behavior of the items cont Tell them about the statement of financial position and the income statement for the 2017 and 2018 periods through the percentage analysis and financial ratios. This research aims to contribute to the companies in this area, in their administration and accounting management, also to the constant practice of quality management that serves as a reference instrument for economic and financial policies in this construction company, which served as an analysis unit, allowing to improve the processes of accounting management, inventory control, cash control, control of the accounts receivable of the company, also aims to encourage the planning of construction services and improving their quality through a constant supervision in the work process. At the end of the investigation it was determined that if there is influence of the quality of service on the profitability of the real estate projects of the Construction Companies in the District of El Tambo 2018., it was also described, that the management of quality of service is good but the Accounting management is still incipient in our analysis unit Consorcio Arquitectos & Ingenieros SAC, it was also recommended to motivate entrepreneurs in the construction sector to formalize their financial accounting information that over time will benefit the company economically.